INTERPERSONAL COMMUNICATION PATTERNS IN DEVELOPING EXCELLENT CHARACTER THROUGH STUDENT DISCIPLINE IN ISLAMIC BOARDING SCHOOLS - Sari Dea Ika Meilani; Suyono Suyono; Almaydza Pratama Abnisa (Sekolah TInggi Ilmu Dakwa dan Komunikasi Islam (STIDKIS) Al Mardliyyah Pamekasa, 2025)
This study aims to understand the methods of interpersonal communication applied by administrators in developing positive character in students through the implementation of discipline at Al-Mar’atush Sholihah Islamic Boarding School, Depok. The background of this study is the importance of interpersonal communication in supporting students, not only in academic aspects but also in moral and character development. Interpersonal communication serves as the primary foundation in the process of cultivating consistent disciplinary behavior. This research employs a qualitative approach with a descriptive method. Data were collected through direct observation, in-depth interviews, and document analysis. The results indicate that the administrators implement interpersonal communication patterns that include emotional bonding, personal approaches, and role modeling in daily activities. The forms of communication used involve both verbal and nonverbal actions, delivered in a polite and educational manner. Obstacles encountered in the character-building process through interpersonal communication were identified as minimal, considering the relatively small number of students, which allows for more intensive guidance. Minor challenges mainly arise from external cultural influences brought by students after holidays, such as interest in K-pop. However, the administrators successfully redirected students’ attention and motivation toward learning through encouraging and educational communication. The study concludes that the interpersonal communication patterns implemented by the administrators play a significant and effective role in shaping students’ excellent character through the disciplinary habits instilled in boarding school life.